A dynamic 3‐factor survival model for acute myeloid leukemia that accounts for response to induction chemotherapy. Issue 9 (30th June 2022) - Tefferi, Ayalew; Gangat, Naseema; Al‐Kali, Aref; Alkhateeb, Hassan; Shah, Mithun; Patnaik, Mrinal S.; Elliott, Michelle A.; Hogan, William J.; Litzow, Mark R.; Hook, Christopher C.; Mangaonkar, Abhishek; Viswanatha, David; et al.
Abstract: The current study was approached with the assumption that response to induction chemotherapy, in acute myeloid leukemia (AML), overshadows pre‐treatment risk variables in predicting survival and therefore be used as an anchor for a simplified risk model. We considered 759 intensively‐treated patients with AML, not promyelocytic: median age 60 years; primary 66%, secondary 25%, and therapy‐related 9%; European LeukemiaNet cytogenetic risk category favorable 8%, intermediate 61%, and adverse 31%. Complete remission with (CR) or without (CRi) count recovery was achieved in 608 (80%) patients. After a median follow‐up of 22 months, 503 deaths, 272 relapses, and 257 allogeneic hematopoietic stem cell transplants (AHSCTs) were recorded. Multivariable analysis identified failure to achieve CR/CRi (HR 3.8, 95% CI 3.1–4.8), adverse karyotype (2.2, 1.8–2.8), and age >55 years (2.1, 1.6–2.7) as main risk factors for survival. HR‐weighted scoring resulted in four‐tiered risk stratification: low (0 points; N = 183), intermediate‐1 (1 point; N = 331), intermediate‐2 (2 points; N = 117), and high (≥3 points; N = 128), with respective median survival (5‐year rate) not reached (68%), 34 (37%), 13 (20%), and 5 (5%) months ( p < .001). FLT3 ‐ITD mutation was associated with inferior survival in intermediate‐1 ( p = .004) and TP53 in intermediate‐2 ( p = .06) and high ( p = .02) risk disease; the latter was fully accounted for by the close association between TP53 mutation and complex/monosomal karyotype while the observations regarding FLT3 ‐ITD were not affected by treatment with midostaurin. AHSCT had a favorable impact on survival, most apparent in intermediate‐1 ( p < .001), intermediate‐2 ( p = .03), and high ( p = .01) risk disease. The proposed 3‐factor survival model offers a novel prototype that is amenable to further enhancement by molecular information and was validated in an external cohort of 1032 intensively‐treated AML patients.